Persistent incisional pain at 1 year after craniotomy: a retrospective observational study - Phoowanakulchai S. (2023)
Background: There have been few reports on persistent incisional pain at 1 year after craniotomy. Hence, this study aimed to explore the distribution of pain at 1 year after elective craniotomy and its related factors. Methods: This retrospective study included data prospectively collected to assess postoperative functional disability. We included patients aged > 55 years at the time of recruitment for our initial study and who had complete data regarding the pain numeric rating scale (NRS) score at 1 year post craniotomy. The primary outcome was the pain NRS score, which was assessed at the postanesthetic clinic as well as at 3 months and 1 year after craniotomy. Multivariable negative binomial regression analysis was performed to analyze the relationship between the pain NRS score at 1 postoperative year and 12 clinically meaningful covariates. These included the Short Form-8 scores for bodily pain and mental health, with higher scores indicating better health. Results: We analyzed data from 102 patients. The mean (95% confidence interval) pain NRS scores at the three measurement points were 2.8 (2.3–3.3), 1.2 (0.8–1.6), and 0.6 (0.3–0.8), respectively. Multivariable analysis revealed that preoperative bodily pain (risk ratio, 0.93; 95% confidence interval, 0.88–0.98) and the pain NRS score at the postanesthetic clinic (risk ratio, 1.32; 95% confidence interval, 1.14–1.52) were associated with the risk of persistent pain at 1 postoperative year. Conclusions: The pain score at 1 year after elective craniotomy was minor; however, preoperative bodily pain and postoperative pain scores were significantly related factors.